Pekendo Mystery Box Media to Improve Fourth Grade Science and Social Learning Outcomes for Elementary School Students - Farha Alina, Kunti; Moh. Fathurrahman (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The lack of science learning media causes students to find it challenging to learn. This has an impact on low learning outcomes. This research aims to develop the Mistery Box Pekendo learning media for fourth-grade elementary school students on material about the Spread of Kingdoms in Indonesia. This type of research is Research and Development (R&D) using the Borg and Gall development model. The product's feasibility is tested by material expert validators, media experts, and users (teachers). The research subjects were 20 grade IV SDN students. Data collection methods in the research were interviews, observation, tests, questionnaires and documentation. Data collection instruments use questionnaires and test questions. The techniques used to analyze data are qualitative descriptive analysis and quantitative and inferential statistics. The research results are that the assessment from media experts is 95% (very feasible), and material experts are 83% (very feasible). The t-test results show differences in student learning outcomes after applying the mystery box pekendo media in learning science material. The results of the N-Gain test show that the increase in student learning outcomes is moderate. It was concluded that the mystery box pekendo media in learning science material is suitable for use and is effective in improving the learning outcomes of fourth-grade elementary school students. The implication of this research is that the media developed helps students learn.